2018
DOI: 10.4328/jcam.5629
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of serum alpha-1-antitrypsin and vitamin B12 levels in patients with vitamin B12 deficiency

Abstract: Comparison of serum alpha-1-antitrypsin and vitamin B12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…One of the protective factors of lung tissue is alpha-1-antitrypsin (A1AT), a proteinase inhibitor [14] . In the literature, it was claimed in some studies that vitamin B12 treatment leads to an increase in A1AT levels [15] . In addition, vitamin B12 deficiency has also been associated with increased levels of homocysteine which is among the cardiovascular risk factors [16] [17] [18] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the protective factors of lung tissue is alpha-1-antitrypsin (A1AT), a proteinase inhibitor [14] . In the literature, it was claimed in some studies that vitamin B12 treatment leads to an increase in A1AT levels [15] . In addition, vitamin B12 deficiency has also been associated with increased levels of homocysteine which is among the cardiovascular risk factors [16] [17] [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Yine sildenafil kullanan hastalarda görülen ağız ve göz kuruluğu yan etkilerinin vitamin B12 yetersizliğinde daha ağır ve uzun süreli olduğu iddia edilmektedir (31). Bütün bunlara ilave olarak serum vitamin B12 seviyeleri ile alfa-1-antitripsin arasında korelasyon olduğu ve vitamin B12 tedavisi alanlarda alfa-1-antitripsin seviyelerinin arttığı ileri sürülmüştür (32).…”
Section: Introductionunclassified
“…There are studies suggesting that the prevalence of obesity is increased in patients with vitamin B12 deficiency (6,7). It is claimed that vitamin B12 may play a role in the synthesis of an antiprotease, alpha-1-antitrypsin (A1AT), and A1AT may be associated with obesity (8). It was suggested that there is a negative correlation between vitamin B12 and serum triglyceride levels and a positive correlation between HDL levels (9,10).…”
Section: Introductionmentioning
confidence: 99%